Regulatory T cells in Systemic Lupus Erythematosus and Pregnancy. (8th February 2013) - Tower, Clare; Mathen, Stephy; Crocker, Ian; Bruce, Ian N.
Abstract : Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disorder that predominantly affects women of reproductive age. As clinical outcomes improve, pregnancy in these women is becoming more common. Although epidemiological data have documented an improvement in the prognosis of pregnancy in these women over recent years, they are still at significantly increased risk of pregnancy complications, such as miscarriage, stillbirth, pre‐eclampsia and impaired foetal growth. The pathogenesis of SLE involves marked immune dysfunction, and in particular, the function of immunosuppressive elements of the immune system is impaired, including regulatory T‐cell function. Because regulatory T cells are likely to be the key cell‐modulating feto‐maternal tolerance, this review overviews the possibility that regulatory T‐cell impairments contribute to pregnancy pathology in women with SLE and contribute to the clinical challenge of managing these women during pregnancy.